Biodegradation of 3,5-dinitrosalicylic acid by Phanerochaete chrysosporium - Madaj, Rafał; Kalinowska, Halina; Sroczyński, Witold; Szeląg, Jakub; Sobiecka, Elżbieta (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2018)
Despite intensive efforts put on prevention of environment pollution by nitroaromatic compounds, these xenobiotics have not been eliminated from the biosphere. The physicochemical properties make nitroaromatics extremely recalcitrant to biodegradation. Therefore, microbial degraders of these pollutants are sought after. This paper reports preliminary results of the study on degradation of 3,5-dinitrosalicylic acid (DNS) by a basidiomycetous fungus Phanerochaete chrysosporium under stationary conditions in a culture medium containing 0.05–0.5% v/v of DNS. The results obtained suggest that the fungus degrades DNS through the reductive pathway.